PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE THINK PAIR SHARE (TPS) UNTUK MENINGKATKAN HASIL BELAJAR ILMU PENGETAHUAN ALAM (IPA) SISWA KELAS V SD NEGERI 12 KECAMATAN BENGKALIS KABUPATEN BENGKALIS - Jasma, Safri; Lazim. N, Lazim. N; Kurniaman, Otang (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This research is motivated by the low learning outcomes fifth grade science students of SD Negeri 12 Bengkalis, with an average grade 67.81. While the value of a minimum completeness criteria (KKM) IPA is 75. Among the students who totaled 32 people, only 13 people (40 625%), which reached the KKM and 19 people (59 375%) who have not reached the KKM. This study is a Classroom Action Research (CAR) conducted aims to improve learning outcomes fifth grade science students of SD Negeri 12 Bengkalis by applying cooperative learning model Think Pair Share (TPS). Data collection instruments in this thesis is the teacher and student activity sheets and learning outcomes. This thesis presents the results of studying the data obtained from the average results of study before action 67.81 increased 4.37% to 70.78 in cycle I. In the second cycle increased by 9.04% with an average of 77.18 after learning outcomes action. The activities of teachers at the first meeting of the first cycle to obtain a percentage of 70.45% with the good category, at the second meeting with a percentage increase of 75.00% both categories. Furthermore, the first meeting of the second cycle of the teacher's activities also increased the percentage becomes 90.90% with a good category and at the second meeting of the second cycle increased again with a percentage of 95.45% excellent category. Student activity at the first meeting of the first cycle to obtain the percentage of 63.63% both categories, at the second meeting have increased the percentage of 70.45% into both categories, at the first meeting of the second cycle increased with the percentage of 81.81% excellent category. At the second meeting of the second cycle increased with the percentage of 93.18% excellent category. Results of the study in class V SD Negeri 12 Bengkalis prove that the implementation of cooperative learning model Think Pair Share (TPS) can improve learning outcomes fifth grade science students of SD Negeri 12 Bengkalis.Keywords: Cooperative type Think Pair Share, Science Learning Outcomes